2011
DOI: 10.1007/s00125-011-2350-y
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy deficiency in beta cells leads to compromised unfolded protein response and progression from obesity to diabetes in mice

Abstract: Aims/hypothesis The unfolded protein response (UPR) in endoplasmic reticulum (ER) and autophagy are known to be related. We investigated the role of autophagy in UPR of pancreatic beta cells and the susceptibility of autophagydeficient beta cells to the ER stress that is implicated in the development of diabetes. Methods Rat insulin promoter (RIP)-Cre + ;autophagy-related 7 (Atg7) F/W mice were bred with ob/w mice to derive RIP-Cre + ;Atg7 F/F -ob/ob mice and to induce ER stress in vivo. GFP-LC3 + -ob/ob mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
147
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(156 citation statements)
references
References 38 publications
8
147
1
Order By: Relevance
“…Again, we observed increased autophagic flux in the liver of leupeptin-treated ob/ob mice. We have also observed that autophagy level and autophagic activity were increased by lipid injury in other types of tissues such as pancreatic islets 45 . Therefore, our data show that both autophagy level and autophagic activity are increased by lipid or obesity in multiple organs in vivo.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Again, we observed increased autophagic flux in the liver of leupeptin-treated ob/ob mice. We have also observed that autophagy level and autophagic activity were increased by lipid injury in other types of tissues such as pancreatic islets 45 . Therefore, our data show that both autophagy level and autophagic activity are increased by lipid or obesity in multiple organs in vivo.…”
Section: Discussionmentioning
confidence: 60%
“…Degradation of long-lived proteins was measured essentially as previously described 45 with modifications. Briefly, cells were plated in collagencoated plates for 24 h. Cells were then labelled with 0.5 mCi ml À 1 C 14 -leucine (Perkin Elmer) for 16 h. After culture for 2 h in a chase medium to allow degradation of short-lived proteins, cells were incubated with serum-free medium containing 2 mM unlabelled leucine and lipid (PA or OA) in the presence or absence of 10 mg ml À 1 each of E64d/pepstatin A and 20 mM NH 4 Cl at 37°C for 3B6 h. Aliquots of the medium were precipitated with trichloroacetic acid, and proteolysis was measured as the percentage of released radioactivity relative to the initial cellular radioactivity.…”
Section: Methodsmentioning
confidence: 99%
“…This rendered autophagy-impaired beta cells hyper-susceptible to apoptosis in response to ER stress. Furthermore, autophagy deficiency prevented the compensatory increase in beta cell mass in response to HFD and in ob/ob mice, resulting in further deterioration of glucose tolerance [75,76]. These studies convincingly show that basal autophagy is not only indispensable for maintaining beta cell mass and function, but is also required for beta cell compensation to obesity-induced insulin resistance.…”
Section: Autophagy In Beta Cell Physiology and Diabetesmentioning
confidence: 62%
“…Reminiscent of the situation in adipose tissue, an increased number of autophagosomes and autophagolysosomes was observed in the beta cells of different models of type 2 diabetes, including ob/ob and db/db mice [75,76] and Akita mice [10]. In Zucker diabetic fatty rats and in insulinoma cells, hyperglycaemia and oxidative stress led to the accumulation of polyubiquitinated protein aggregates that were degraded by autophagy [77].…”
Section: Autophagy In Beta Cell Physiology and Diabetesmentioning
confidence: 99%
See 1 more Smart Citation